2022
DOI: 10.3389/fphar.2022.956093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postoperative adjuvant steroid therapy on the outcomes of biliary atresia: A systematic review and updated meta-analysis

Abstract: Background: Postoperative adjuvant steroid therapy is regarded as the conventional treatment for patients with biliary atresia (BA) who have undergone Kasai portoenterostomy (KP). However, whether the steroid therapy can improve BA outcomes is controversial. This meta-analysis aimed to evaluate the effects of adjuvant steroid therapy on the surgical prognosis of BA.Methods: We searched related studies published in PubMed, Embase, Web of Science, Cochrane, and the Chinese National Knowledge Infrastructure datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Being a retrospective analysis, we took available bilirubin level closest to 3 months (within 3 weeks) which in some instances might have been too early. Majority of our sample have not received adjuvant steroids which have shown to improve jaundice clearance [12,13]. Studies have shown in CMV -associated biliary atresia COJ can be as low as 15% [14] .Exact prevalence of congenital CMV infection in Sri Lanka is not known but postulated to be much higher than in western countries [15].…”
Section: Resultsmentioning
confidence: 97%
“…Being a retrospective analysis, we took available bilirubin level closest to 3 months (within 3 weeks) which in some instances might have been too early. Majority of our sample have not received adjuvant steroids which have shown to improve jaundice clearance [12,13]. Studies have shown in CMV -associated biliary atresia COJ can be as low as 15% [14] .Exact prevalence of congenital CMV infection in Sri Lanka is not known but postulated to be much higher than in western countries [15].…”
Section: Resultsmentioning
confidence: 97%
“…Adjuvant steroid therapy has become popular for the postoperative management of biliary atresia in infants ( 6 , 23 ) because steroid therapy improves jaundice clearance. However, it has been questioned that postoperative steroid therapy did not bring certain benefits for patients with biliary atresia in some studies ( 24 ). Due to the inconsistency of previous research results, the impact of postoperative steroid treatment on the prognosis of biliary atresia patients is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, the use of steroids is widely adopted for its anti-inflammatory effect and promotion of bile flow. A recent RCT and meta-analysis both confirmed that postoperative adjuvant steroid therapy improved bile drainage and native liver survival 161 , 162 . Recurrent cholangitis is another significant factor which negatively affects native liver survival.…”
Section: Hepatobiliarymentioning
confidence: 91%